2015
DOI: 10.1007/s12263-015-0499-6
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and soybean-derived bioactive molecules attenuate the expansion of stem cell-like epithelial subpopulation and confer apoptotic sensitivity in human colon cancer cells

Abstract: Colorectal cancer (CRC) is a disease whose genesis may include metabolic dysregulation. Cancer stem cells are attractive targets for therapeutic interventions since their aberrant expansion may underlie tumor initiation, progression, and recurrence. To investigate the actions of metabolic regulators on cancer stem cell-like cells (CSC) in CRC, we determined the effects of soybeanderived bioactive molecules and the anti-diabetes drug metformin (MET), alone and together, on the growth, survival, and frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
7
27
0
Order By: Relevance
“…The activity of Lunasin both in vitro and in vivo on melanoma CICs suggests the intriguing possibility that Lunasin can target these quiescent and drug-resistant cells and is consistent with a recently published study on colon cancer [33]. These studies demonstrated that putative CICs isolated based on the expression of the surface markers CD133 and CD44 were sensitive to Lunasin and that this effect likely involves modulation of the PTEN/PI3K/FASN axis [33]. Taken in combination with our results, these data support a novel hypothesis that Lunasin and other soy derivatives have the ability to decrease cancer stem cell populations.…”
Section: Discussionsupporting
confidence: 87%
“…The activity of Lunasin both in vitro and in vivo on melanoma CICs suggests the intriguing possibility that Lunasin can target these quiescent and drug-resistant cells and is consistent with a recently published study on colon cancer [33]. These studies demonstrated that putative CICs isolated based on the expression of the surface markers CD133 and CD44 were sensitive to Lunasin and that this effect likely involves modulation of the PTEN/PI3K/FASN axis [33]. Taken in combination with our results, these data support a novel hypothesis that Lunasin and other soy derivatives have the ability to decrease cancer stem cell populations.…”
Section: Discussionsupporting
confidence: 87%
“…For mammosphere formation assay, cells (2.5 × 10 3 cells/well) were plated in 6-well low-attachment plates after 24h Dox treatment and then evaluated for numbers of spheroids (mammospheres) 5 days later, in the absence of additional treatments, as previously described (Montales et al 2012). Cell viability using cells plated at an initial density of 2 × 10 5 per well was measured by the trypan blue exclusion method using the Vi-Cell cell viability analyzer (Beckman Coulter Inc., Atlanta, GA) (Montales et al 2015). The percent of apoptotic cells was evaluated 48h post-treatment by Annexin V staining (Trevigen, Gaithersburg, MD), followed by analyses using a Becton-Dickinson LSRFortessa Flow Cytometer (BD Biosciences, San Jose, CA) (Montales et al 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability using cells plated at an initial density of 2 × 10 5 per well was measured by the trypan blue exclusion method using the Vi-Cell cell viability analyzer (Beckman Coulter Inc., Atlanta, GA) (Montales et al 2015). The percent of apoptotic cells was evaluated 48h post-treatment by Annexin V staining (Trevigen, Gaithersburg, MD), followed by analyses using a Becton-Dickinson LSRFortessa Flow Cytometer (BD Biosciences, San Jose, CA) (Montales et al 2015). For all assays, treatment effects were determined from three independent experiments in triplicates, with each experiment representing a distinct T-MEC isolation.…”
Section: Methodsmentioning
confidence: 99%
“…Synergy was found with paclitaxel and carboplatin in prostate and lung CSCs murine xenografts [101]. For phytochemicals, Montales et al (2015) reported that metformin and genistein targeted colon CSC spheroid formation and proliferation, and the combination increased the effectiveness of 5-FU [102]. Ning et al (2016) reported that both curcumin and metformin individually inhibited pancreatic CSC spheroids [103], the two compounds should be tested as a combination.…”
Section: Metforminmentioning
confidence: 99%